2018
DOI: 10.3892/ol.2018.7850
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic analysis of patients with locally advanced nasopharyngeal carcinoma following intensity modulated radiation therapy

Abstract: Abstract. The present study retrospectively analyzed the prognostic factors of 135 patients with locally advanced nasopharyngeal carcinoma (NPC) who received intensity modulated radiation therapy between August 2008 and January 2012 at Xiangya Hospital of Central South University. Patients were staged from III-IVA according to the 7th American Joint Committee on Cancer staging system. Using Statistical Analysis System 9.3 software, the present study demonstrated that, among these 135 patients, the 5-year overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In this study, we found that paranasal sinus invasion and cervical lymphatic metastasis were independent negative prognostic factors for OS, PFS, and DMFS and that GTVnx-residual was an independent negative prognostic factor for OS. Our previous studies confirmed that the distance between the primary tumor and brain stem and residual nasopharyngeal carcinoma after chemotherapy are important factors that affect the survival of NPC patients (17,18). Here, we found that the OS, PFS, DMFS, and LRFS did not differ between patients with paranasal sinus invasion and T3 disease and those with T4.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, we found that paranasal sinus invasion and cervical lymphatic metastasis were independent negative prognostic factors for OS, PFS, and DMFS and that GTVnx-residual was an independent negative prognostic factor for OS. Our previous studies confirmed that the distance between the primary tumor and brain stem and residual nasopharyngeal carcinoma after chemotherapy are important factors that affect the survival of NPC patients (17,18). Here, we found that the OS, PFS, DMFS, and LRFS did not differ between patients with paranasal sinus invasion and T3 disease and those with T4.…”
Section: Discussionsupporting
confidence: 84%
“…The c-index was also calculated using R 3.6.0 software. The P -value of the c-index was obtained using the two-tailed paired t -test, calculated according to the rcorrp.cens function in the Hmisc package ( 16 , 17 ). P <0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 For non-metastatic NPC, the 5-year overall survival (OS) has been reported to be between 62% and 90%. [3][4][5][6] The tumor-node-metastasis (TNM) staging system is the most widely used system for predicting the survival of NPC patients; however, due to the intrinsic heterogeneity of tumor cells, and because intratumor microenvironments are not considered in the TNM staging system, personalized biomarkers for the pathogenesis or progression of NPC are needed to predict patient survival more accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Still, nasopharyngeal carcinomas are commonly diagnosed in Asia, especially in China [the crude incidence rate was 3.26/100,000 ( 2 )]. Radiotherapy remains the standard treatment for these generally radiosensitive tumors and current estimates of 5-year overall survival after radiotherapy range from 66% to 83% ( 3 ). Given these promising survival rates, oncologists increasingly have focused on the quality of life of their patients.…”
Section: Introductionmentioning
confidence: 99%